2020
DOI: 10.1371/journal.pone.0237999
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of clinical features and genetic variants in mevalonate kinase (MVK) gene of South Indian families suffering from Hyperimmunoglobulin D Syndrome

Abstract: Hyper-IgD syndrome (HIDS, OMIM #260920) is a rare autosomal recessive autoinflammatory disorder caused by pathogenic variants in the mevalonate kinase (MVK) gene. HIDS has an incidence of 1:50,000 to 1:5,000, and is thought to be prevalent mainly in northern Europe. Here, we report a case series of HIDS from India, which includes ten patients from six families who presented with a wide spectrum of clinical features such as recurrent fever, oral ulcers, rash, arthritis, recurrent diarrhea, hepatosplenomegaly, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 64 publications
(99 reference statements)
0
22
0
Order By: Relevance
“…A number of studies have shown that this variant was present in homozygous or compound heterozygous states in multiple patients affected by HIDS with different ethnic backgrounds. Various in-vitro and in-vivo functional studies have proved that p.V377I is disease-causing with a very low allele frequency in control databases ( Drenth et al, 1999 ; Houten et al, 1999 , 2001 ; Cuisset et al, 2001 ; Levy et al, 2013 ; Govindaraj et al, 2020 ). The fourth nonsynonymous likely pathogenic variant has been found in RAB27A i.e., Arg82Cys (R82C), and had been predicted as a causal variant for hemophagocytic lymphohistiocytosis (HLH) (OMIM number 267700).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that this variant was present in homozygous or compound heterozygous states in multiple patients affected by HIDS with different ethnic backgrounds. Various in-vitro and in-vivo functional studies have proved that p.V377I is disease-causing with a very low allele frequency in control databases ( Drenth et al, 1999 ; Houten et al, 1999 , 2001 ; Cuisset et al, 2001 ; Levy et al, 2013 ; Govindaraj et al, 2020 ). The fourth nonsynonymous likely pathogenic variant has been found in RAB27A i.e., Arg82Cys (R82C), and had been predicted as a causal variant for hemophagocytic lymphohistiocytosis (HLH) (OMIM number 267700).…”
Section: Discussionmentioning
confidence: 99%
“…13–14). Three patients were found to have the V377I Dutch founder variant and 2 had c.1129G>A variant which is fairly common in South India particularly Kerala ( 15 ).…”
Section: Clinical Profile Of Patients With Defects Affecting the Inflammasomesmentioning
confidence: 99%
“…Further, molecular insights of these disorders have provided the basis for new therapeutic interventions leading to improved outcomes and long-term survivals. There is paucity of data on SAID from India with published literature comprising of only anecdotal case reports (14)(15)(16)(17)(18)(19)(20)(21). In this manuscript we describe clinical features, molecular profile, treatment and outcome in patients with monogenic SAID from six centers in our country.…”
Section: Introductionmentioning
confidence: 99%
“…Serum IgD have been suggested to increase in patients with inflammatory autoimmune diseases, such as systemic lupus erythematosus (SLE) 29 and rheumatoid arthritis 30 , and in hereditary autoinflammatory syndromes, most notably the hyper-IgD syndrome (HIDS) [31][32][33][34] . In healthy humans, many B cells with CSR to IgD react with components of the self 35 .…”
Section: B Cell Rad52 Phosphorylation Increased Csr To Igd and Igd Autoantibodies In Systemic Autoimmunitymentioning
confidence: 99%
“…Serum IgD have been suggested to increase in patients with inflammatory autoimmune diseases, such as systemic lupus erythematosus (SLE) 29 and rheumatoid arthritis 30 , and in hereditary autoinflammatory syndromes, most notably the hyper-IgD syndrome (HIDS) [31][32][33][34] . While in healthy humans, many B cells make IgD that react with components of the self 35 , we found patients with systemic lupus to display significantly higher levels of circulating IgD, including IgD specific for nuclear antigens, than their healthy subject controls (Fig.…”
Section: B Cell Rad52 Phosphorylation Increased Csr To Igd and Igd Autoantibodies In Systemic Autoimmunitymentioning
confidence: 99%